Pengaruh Pendidikan Kesehatan Terhadap Kecemasan Tentang Menarche pada Siswi Kelas V Sekolah Dasar - Anggi Winarti; Fatma Siti Fatimah; Wahyu Rizky (Alma Ata University Press, 2017)
Menarche is part of the primary change that commonly affects the psychology of a child. The psychological impact of menarche can be in a form of anxiety which lead to many problems to children. Based on research Randomination of childhood BMI and Early Menarche gained the results of girls who experience her first menarche changes in her either psychic like arise a sense of anxiety and happened changes such obesity. Anxiety is the most common, noticeable symptom in children during menarche and it is sometimes reinforced the desire to reject the physiological process. Anxiety can be influenced by age, genetics, level of knowledge and others.  Provision of information about menstrual health through education is one way to deal with the symptoms of psychological disorders that arise when facing menarche. Objective: to determine the effect of health education of anxiety in menarche in students at 5th grade Sonosewu Elementary School and Muhammadiyah Ambarbinangun Elementary School. This study uses quasi experiment research to control time series design or the sample material eqievalent design. The sample in this study is at 5th grade students in Sonosewu Elementary School 15 and Muhammadiyah Ambarbinangun Elementary School 15 who are not having menstruation yet, in total of 30 students, taken using total sampling technique. Data were collected using a questionnaire and analyzed using the Wilcoxon test. Results showed that p-value 0.023 experimental group and p-value 0.234 the control group (<0.05). And from statistical test, the result showed that the differentiation was meaningful on intervention group. In conclusion, there was a significant influence of health education toward the anxiety about menarche in 5th grade students.